Analisis Kadar Rhodamin B Pada Blush-On Menggunakan Metode Spektrofotometri Uv-Vis - Taupik, Muhammad; Adam Mustapa, Moh; Sitti Gonibala, Sintia (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
Cosmetic are mixture of materials that are ready to be used on the outside of the body. One type cosmetics makeup that is often used is Blush-On. This Blush-On cosmetics has a distinictive red color, so it issu red color, so it is suspected that there is still a misuse in the addition of Rhodamine B to Blush—n cosmetics, especially cosmetics that are not registered to BPOM (The Nationalof Drug and Food Control). Based on the PERMENKES RI No. 445/Menkes/Per/V1998 concerning certain dyes declared dangerous it is a synthetic dye Rhodamine B which is one of the dyes that is prohibited for use in-cosmetics products because the fidings of BPOM from 2014 to 2015, Rhodamine B is still used as one of the dyes. This study aims to knowthe misuse of the addition of synthetic dye Rhodamine B to Blush-On cosmetics and to know how much Rhodamine B is contained in the Blush-On cosmetic samples. The results of the qualitative test with the staining method on the Blush-On cosmetics samples A,B,C,D, and E, it is sample E that produces a clear reddish color that has he potential to contain Rhodamine B . Furthemore, it is continued with a quantitative test by using Uv-Vis Spectrofotometry, and it obtains levels of Rhodamine B in sample E is 9,98mquantitative test by using Uv-Vis Spectrofotometry, and it obtains levels of Rhodamine B in sample E is 9,98mg/g.